2018
DOI: 10.3762/bjoc.14.121
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt–metalloid alloys for electrochemical oxidation of 5-hydroxymethylfurfural as an alternative anode reaction in lieu of oxygen evolution during water splitting

Abstract: The electrochemical water splitting commonly involves the cathodic hydrogen and anodic oxygen evolution reactions (OER). The oxygen evolution reaction is more energetically demanding and kinetically sluggish and represents the bottleneck for a commercial competitiveness of electrochemical hydrogen production from water. Moreover, oxygen is essentially a waste product of low commercial value since the primary interest is to convert electrical energy into hydrogen as a storable energy carrier. We report on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 37 publications
0
54
0
Order By: Relevance
“…Current densities up to hundreds of mA cm −2 were reported for both catalysts at potentials lower than 1.4 V, making HMF oxidation a promising anodic counter reaction for cathodic HER. In another study, Co‐based electrocatalysts showed 100 % conversion of HMF to FDCA with 90 % FE but at higher overpotentials than the Ni‐based electrocatalysts.…”
Section: Key Challenges For Alternative Oxidation Reactionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Current densities up to hundreds of mA cm −2 were reported for both catalysts at potentials lower than 1.4 V, making HMF oxidation a promising anodic counter reaction for cathodic HER. In another study, Co‐based electrocatalysts showed 100 % conversion of HMF to FDCA with 90 % FE but at higher overpotentials than the Ni‐based electrocatalysts.…”
Section: Key Challenges For Alternative Oxidation Reactionsmentioning
confidence: 96%
“…) and on CoB/NF (orange—dot line) (adapted with permission from Ref. ). b) Overview of alcohol electrooxidation reactions and important target products and their application domain.…”
Section: Key Challenges For Alternative Oxidation Reactionsmentioning
confidence: 99%
“…Especially in the recent years, some research groups highlighted promising potentials by integrating the HER with electrochemical HMF oxidation for simultaneous H 2 generation and oxidative HMF upgrading. [57][58][59][60] A representative advance in this research field was reported by Sun's group in 2016. [58] They demonstrated a bifunctional catalytic electrode based on 3D Ni 2 P nanoparticle arrays on Ni foam (Ni 2 P NPA/NF) to couple HMF oxidation and HER.…”
Section: Coupling Her With Aldehyde Oxidation Reactionsmentioning
confidence: 98%
“…In this context, transition‐metal‐based electrocatalysts, especially compounds or alloys of Ni and Co with main‐group elements ( e. g., P and S) as well as layered double hydroxides (LDHs), were reported to be efficient electrocatalysts for the selective oxidation of HMF to target products, achieving high conversions and yields. Especially in the recent years, some research groups highlighted promising potentials by integrating the HER with electrochemical HMF oxidation for simultaneous H 2 generation and oxidative HMF upgrading …”
Section: Electrocatalytic H2 Production From Water Assisted By Varioumentioning
confidence: 99%
“…Driven by the electrochemical potential, more and more innovative and cheap catalysts developed from earth-abundant transition metals, such as Ni 2 P [133], CoP [134], Ni 2 S 3 [135], porous Ni [136], Ni x B [137], CoB [138], NiB x [139], NiCo 2 O 4 [140,141], VN [142], Ni 3 N@C [143], Ni/Co/Fe oxyhydroxides [144], Ni/NiOOH [145], nanocrystalline Cu foam [146], CuNi(OH) 2 /C [147], NiSe@NiO x [148], NiFe-LDH [127], and Cu x S@NiCo-LDH [149], were reported to be more efficient than noble metal catalysts, reversing the situation that the precious metal catalysts are more active and popular than the transition metal catalysts in HMF thermocatalytic oxidation. Grabowski et al [132] firstly reported the HMF electrooxidation into FDCA on NiOOH anode, realizing 71% FDCA yield with 84% faradaic efficiency (FE) in a divided H-shape electrolyzer with 1 M NaOH aqueous electrolyte.…”
Section: Electrochemical Oxidation By Transition Metal Catalystsmentioning
confidence: 99%